(untitled) (African Journal of Biomedical Research, 2020)
Adverse childhood experience (ACE) portends future consequences on physical, mental and social wellbeing. The impact of ACEs is amplified by stressors, such as academic, physical, social and emotional stressors, which medical students are constantly exposed to. This study is aimed at determining the association between adverse childhood experiences and adult psychosocial wellbeing among preclinical medical students. A cross sectional study was conducted among medical students in the 2nd and 3rd year of study, at the University of Ibadan, Nigeria. Participants completed socio-demographic, an Adverse Childhood Experience, the World Health Organization’s Quality of Life (WHOQOL-BREF) and the Rosenberg’s self-esteem questionnaires. Data obtained were analyzed using SPSS. Descriptive and inferential statistical analyses were performed. A total of 277 respondents with a mean age of 20.1 years (SD=5.6) participated in the study. At least one out of ten categories of ACEs were reported by 40.8% of respondents; physical abuse (19.1%), emotional abuse (18.2%), parental divorce (9.4%) and sexual abuse (9.0%). There was a significant association between adverse childhood experiences and adult psychosocial wellbeing (p<0.05), as well as low self-esteem (p<0.05). Respondents with previous exposure to ACEs were six times more likely to suffer from low esteem compared to non-exposed students (Adj OR:6.3, 95%CI:1.3-31.4, p=0.003). Mother’s (p=0.001) and father’s (p=0.028) level of education, parental separation (p<0.0001), and having lived with step-parent (p=0.009) or other relatives (p=0.041) were associated with exposure to ACEs. This study shows an association between exposure to adverse childhood experiences and adult psychosocial wellbeing among medical students